Leydig cell tumour and mature ovarian teratoma: rare androgen-secreting ovarian tumours in postmenopausal women. (1st November 2016) - Palha, Ana; Cortez, Luísa; Tavares, Ana Paula; Agapito, Ana
Abstract : Androgen-secreting ovarian tumours are extremely rare accounting for <5% of all ovarian neoplasms. They are more frequent in postmenopausal women and should be suspected in the case of a rapid onset of androgenic symptoms. We report 4 cases of postmenopausal women who presented with signs of virilisation. All patients revealed increased serum levels of testosterone, normal dehydroepiandrosterone-sulfate and negative pelvic ultrasound for adnexal masses. An androgen-secreting ovarian tumour was suspected and all of them were submitted to bilateral oophorectomy. Histology confirmed the diagnosis of Leydig cell tumours in 3 patients and mature teratoma in 1. A successful response to surgery, which includes a decline in serum androgen levels and signs of hyperandrogenism, was observed in our patients. This case series demonstrates that androgen-secreting ovarian neoplasms may not be detectable by imaging studies, but should be considered in the differential diagnosis of all postmenopausal women with signs of hyperandrogenism.